EVALUATION OF THE TREATMENT-AND-PROPHYLACTIC COMPLEX EFFICACY DURING INDUCED METABOLIC SYNDROME - Kravchenko, L.S.; Appelhans, O.L.; Poliakov, A.E.; Pasechnyk, О.V.; Borysiuk, I.Yu.; Honcharenko, O.V.; Ivanova, Ya.I. (World of Medicine and Biology, 2021)
The efficacy of the treatment-and-prophylactic complex, which includes phytopreparation based on the dihydroquercetin bioflavonoid – a natural capillary protector, an antioxidant that by its pharmacological action belongs to the group of angioprotectors and a microcirculation corrector, used per os, in combination with local therapy of periodontal tissues with a new dental elixir based on propolis and biologically active substances of plant origin adaptogens with ultraphonophoresis was determined in experiment on 48 white male Wistar rats, aged 2–3 months, weighing (238±10) g. Under induced metabolic syndrome in rats, the use of the treatment-and-prophylactic complex neutralized the negative effects of the components of the pathological condition in the form of improved metabolism with normalization of glucose, triglycerides, cholesterol, anti-inflammatory interleukins level in the blood serum, improved liver condition and periodontal tissues. The treatment-and-prophylactic complex on the background of MS simulation rendered a periodontal-protective effect and had positive influence on systems of antioxidant defence and nonspecific resistance both at the systemic level and in the periodontal tissues.
Keywords: metabolic syndrome; prevention; inflammation; antioxidant protection; periodontium